Charging ahead: Prioritizing renewable energy for electric minibuses in the Philippines - Thomas Stringer; Sandy Mae Gaspay; Varsolo Sunio; Manuel Burelo (Sustainability Analytics and Modeling)
This study evaluates the environmental and economic impacts of transitioning to electric minibuses (e-jeepneys) in the informal transportation sector of the Philippines. Using a comprehensive model that simulates different e-jeepney uptake scenarios and electricity grid configurations, we analyze carbon emissions and energy costs. Data from the 2023 energy grid and vehicle emission standards are utilized to assess various grid scenarios, including net-zero and natural gas options. Our findings reveal that a 10% increase in e-jeepney uptake results in significant reductions in both carbon emissions (36 gCO2/km) and energy costs (0.70 PHP/km) when paired with a decarbonized grid. The study underscores the synergistic benefits of combining e-jeepney adoption with grid decarbonization and suggests that policymakers should pursue integrated strategies to maximize environmental and economic gains.